2011
DOI: 10.2217/nnm.11.44
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/PLGA Particles for Controlled Release of α-Tocopherol in The GI Tract Via Oral Administration

Abstract: In vitro and ex vivo results showed that PLGA and Chi/PLGA nanoparticles were efficiently taken up by the GI tract and could be optimized to deliver α-tocopherol to the intestine and improve its bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 59 publications
3
29
0
1
Order By: Relevance
“…The PLGA control showed a biphasic response as previously reported (76,77) , with an initial burst release followed by a sustained-release period. The addition of chitosan did not alter the release profile but increased the rate of protein release as reported previously (78)(79)(80) . Microparticles containing chit/TPP showed a triphasic release profile with a higher initial rate of release relative to the control.…”
Section: Protein Release From Plga Microparticlessupporting
confidence: 81%
“…The PLGA control showed a biphasic response as previously reported (76,77) , with an initial burst release followed by a sustained-release period. The addition of chitosan did not alter the release profile but increased the rate of protein release as reported previously (78)(79)(80) . Microparticles containing chit/TPP showed a triphasic release profile with a higher initial rate of release relative to the control.…”
Section: Protein Release From Plga Microparticlessupporting
confidence: 81%
“…For example, Arunkumar, Harish Prashanth, and Baskaran (2013) reported that lutein nanoentrapped in chitosan displayed higher bioavailability than unmodified lutein in mice. Poly(lactic-co-glycolic) acid (PLGA) has been used successfully as a biodegradable polymer and is often preferred for NP synthesis because of its well-established safety (Semete et al, 2010) and stability in intestinal environments (Murugeshu, Astete, Leonardi, Morgan, & Sabliov, 2011) as well as its effectiveness as a carrier of hydrophobic compounds (Khalil et al, 2013;Li et al, 2013;Tsai et al, 2011). However, its application with carotenoids has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the great potential advantages of the use of chitosan-coated PLGA (CS-PLGA) nanoparticles as carriers, numerous studies have investigated their transport potential in gene, drug, and vaccine delivery, via various administration routes. [16][17][18][19][20][21][22] However, to our knowledge, no study has yet investigated the potential of CS-PLGA nanoparticles for intestinal delivery of exendin-4 or reported the effect of molecular weight and degree of deacetylation on the characteristics of CS-PLGA nanoparticles.…”
Section: Introductionmentioning
confidence: 99%